EFFICIENCY OF POLYSTYRENE INSULATED CEMENT BLOCKS IN ARID REGIONS - Muawia A Dafalla; Mohammed I. Al Shuraim (GEOMATE Journal, 2018)
Polystyrene insulated cement blocks emerged recently as an energy saving building material in construction practice. Expanded polystyrene of 5cm thickness or more is introduced as a middle fill layer within the cement block in order to improve the thermal properties of walls. This study is made to investigate the efficiency of insulation provided by this type of treatment. Two chambers were constructed in an open area where the walls are subjected to variable weather conditions ranging from moderate to hot weather for a period of three months. The arid region selected was Riyadh, Saudi Arabia. Temperature was found to vary between day and night through this period from as low as 9 ºC to as high as 48 ºC. Each chamber is built in the form of four block walls 20 cm in thickness, one meter wide and one meter high. The chambers were founded on grade slabs with a wood board used as a roof. The two chambers are identical except for the type of blocks; one is built using polystyrene insulated blocks and the other without insulation. Construction was carried out the same way as used in local practice. Thin mortar layer is used for bonding blocks. 5TE sensors and a data logger were used to record ambient temperature and temperature inside each chamber. Hourly records throughout the testing period were used to evaluate and compare the insulated and non-insulated blocks. It was found that the improvement provided by the polystyrene cement blocks is less efficient in hot temperature than in moderate temperature. The insulation provided by the blocks as constructed is very poor and heat transfer is enabled through mortar filled gaps and joints. The temperature gradient has influence on the polystyrene insulation material.